2017
DOI: 10.1590/0366-69132017633662063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the thermal performance of different cold materials for urban paving

Abstract: The phenomenon of the warming of cities at high temperature levels, the so-called "heat island", has been studied around the world. Apart from generating thermal discomfort, this urban phenomenon has been causing an increase in the demand for energy for cooling the environments. In response to the environmental impact generated by this phenomenon, researchers from different nations have developed techniques for warming mitigation, developing new materials, technologies, and constructive systems. In this contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Additionally, it is observed that cristobalite (JCPDS: 075-0923) was contained after calcination treatment (up to 700°C) but it disappears at 1525°C [20]. Contrarily, the signals that were located above 55°2theta corresponded in their great majority to quartz (JCPDS: 46-1045) [21] and mordenite since these phases prevail after calcination at 700°C. Lastly, it was observed that zeolitic structures persisted after the thermal treatment with the exception of heulandite.…”
Section: Results and Conclusionmentioning
confidence: 94%
“…Additionally, it is observed that cristobalite (JCPDS: 075-0923) was contained after calcination treatment (up to 700°C) but it disappears at 1525°C [20]. Contrarily, the signals that were located above 55°2theta corresponded in their great majority to quartz (JCPDS: 46-1045) [21] and mordenite since these phases prevail after calcination at 700°C. Lastly, it was observed that zeolitic structures persisted after the thermal treatment with the exception of heulandite.…”
Section: Results and Conclusionmentioning
confidence: 94%
“…Na cidade de Criciúma SC pesquisadores (CASTRO et al, 2017) investigam a influência da pavimentação urbana e os efeitos com o fenômeno no aquecimento da cidade. O estudo foi desenvolvido com propósito de desenvolver, testar e avaliar novos materiais frios para uso em pavimentação, sendo esse, na visão dos pesquisadores, o fator responsável por significativa contribuição para a ocorrência das ilhas de calor nas cidades, pois os materiais frios apresentam melhor desempenho térmico que os materiais convencionais (como asfalto e concreto).…”
Section: Introductionunclassified